Kearifan Lokal dalam Kesehatan - Yuliarti Yuliarti; Ine Kusuma Aryani; Beny Wijarnako Kertopati (KOLONI, 2023)
This research aims to describe the view of health according to the Jalawastu indigenous people, forms of disease prevention?, and forms of treatment? This research was researched because indigenous people still carry out traditional treatment related to nature conservation and traditional traditions from generation to generation. A qualitative research approach with the case study research method aims to understand social reality, namely seeing the world as it is. Case studies are defined as a method or strategy for uncovering certain cases. Health in the context of indigenous communities has various views, it can be a measure of someone's health or illness as a result of their behavior. The Jalawastu Indigenous People classify diseases into three types, namely ordinary diseases, diseases caused by magic and diseases caused by food. The Jalawastu Indigenous People are very concerned about the balance of nature, they believe that the source of disease is environmental damage, interference from supernatural beings, violations of clothing and customary provisions. The Jalawastu indigenous people respect the environment very highly, this is proven by the Jalawastu people who are still able to maintain the prohibition on storing sewage (septic tanks) in the house, they consider the land of the Jalawastu traditional village to be sacred, there are no septic tanks allowed in their environment, so that defecation or urinating in flowing rivers. In preventing disease, the role of food is not only to fill the stomach but must have good nutritional quality to maintain health. All prohibitions must be obeyed. There are three forms of treatment to treat disease, namely tatangkalan or treatment with plants, stall medicine, and jampe (mantra). To treat common illnesses, some residents still use medicinal plants, although some have switched to using shop medicines, medicines from health centers or referral medicines from doctors.